2021
DOI: 10.3390/cancers13235925
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Preliminary Efficacy of a Web- and Telephone-Based Personalised Exercise Intervention for Individuals with Metastatic Prostate Cancer: The ExerciseGuide Pilot Randomised Controlled Trial

Abstract: Preliminary research has shown the effectiveness of supervised exercise-based interventions in alleviating sequela resulting from metastatic prostate cancer. However, many individuals encounter barriers that limit the uptake of face-to-face exercise. Technology-enabled interventions offer a distance-based alternative. This pilot study aimed to explore the acceptability, safety and preliminary efficacy of a web-based exercise intervention (ExerciseGuide) in individuals with metastatic prostate cancer. Forty par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…Taken together, these results support the program's feasibility. This suggests that, consistent with the findings of other malignancy groups, [23][24][25][26] an eHealth intervention is a feasible way to deliver an exercise intervention to individuals with MM. This program included three key elements which likely bolstered the program's feasibility: (1) tailoring, (2) virtual supervision/active support, and (3) trained personnel.…”
Section: Safety Feasibility and Satisfactionsupporting
confidence: 76%
See 1 more Smart Citation
“…Taken together, these results support the program's feasibility. This suggests that, consistent with the findings of other malignancy groups, [23][24][25][26] an eHealth intervention is a feasible way to deliver an exercise intervention to individuals with MM. This program included three key elements which likely bolstered the program's feasibility: (1) tailoring, (2) virtual supervision/active support, and (3) trained personnel.…”
Section: Safety Feasibility and Satisfactionsupporting
confidence: 76%
“…22 Recent trials have found eHealth interventions to be feasible and acceptable in older adults with cancer, 23,24 individuals with thoracoabdominal malignancies, 25 and individuals with metastatic prostate cancer. 26 Other trials identify the promise of eHealth interventions for outcomes such as fatigue, strength, pain, and functional capacity in various cancer populations. 27,28 The purpose of this study was to determine the safety, feasibility, and preliminary efficacy of a 12-week virtually supported home exercise program.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 26 included trials, one trial was a non-randomised clinical trial [ 8 ] and the remaining 25 were randomised controlled trials (RCT) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Twelve trials (46.2%) assessed only participants with bone metastases; the remaining fourteen (53.8%) included both participants with and without bone metastases.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1777 participants were included in the present review; of which 1319 participants (74.2%) had bone metastases, and 1132 participants (63.7%) were allocated to an exercise intervention ( Figure 2 ). Seventeen trials (65.4%) included participants with prostate cancer [ 8 , 9 , 10 , 11 , 13 , 14 , 15 , 17 , 20 , 21 , 22 , 23 , 24 , 26 , 30 , 31 , 32 ]; 11 trials (42.3%) included participants with breast cancer [ 8 , 10 , 12 , 14 , 17 , 18 , 19 , 20 , 22 , 27 , 34 ]. Trials that recruited participants with mixed tumours (including breast and prostate) accounted for 65.4% (17 trials) [ 8 , 10 , 14 , 17 , 20 , 22 , 25 , 28 , 29 , 32 , 34 ] ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Essentially, IF an individual selects a statement, THEN they will be shown a pre-determined answer. ExerciseGuide UK has been adapted from previous versions of ExerciseGuide [7][8][9][10][11]. A detailed protocol of the adaptation and redevelopment of ExerciseGuide UK has been published [12].…”
Section: Doctoral Research and Exerciseguide Ukmentioning
confidence: 99%